Alone in Space : A Collection - Walden, Tillie, 1996- (London : Avery Hill Publishing, 2021)
"In her first collection of short comics stories, Tillie Walden opens windows into strange new worlds with works such as 'The End of Summer,' 'I Love This Part,' 'A City Inside,' and never-before collected sketches, webcomics, and short comics for magazines"--
I love this part -- The end of summer -- A city inside.
Keywords: Self-realization -- Comic books, strips, etc; Sick -- Comic books, strips, etc; Love -- Comic books, strips, etc; Adulthood -- Comic books, strips, etc; Self-realization -- Fiction; Sick -- Fiction; Love -- Fiction; Adulthood -- Fiction; Graphic novels; Short stories